ASPEK ETIKA DALAM PENGGUNAAN KECERDASAN BUATAN (AI) DALAM LAYANAN PERBANKAN SYARIAH - Anggi Dwi Larah; Nabila Safutri Siregar, Tasya Salsabila, Ma’arif Noer Lubis, Nurbaiti (Adisam Publisher, 2023)
The emergence of Artificial Intelligence (AI) technology or what we usually call artificial intelligence is one of the new developments that can emerge from the Industrial Revolution 4.0, the fourth industrial transformation which is characterized by rapid technological development and interconnectivity. between technological development and its use. This research aims to examine the challenges and opportunities of AI in the banking sector. This type of research uses a qualitative approach and is descriptive in nature. Using the literature study method, research data was collected from relevant publications, journals and papers. Relevant literary papers were collected and presented as part of the data analysis process. The findings of this research show that AI has an important role in the development of banking in Indonesia, especially in the field of open banking, which is replacing closed banking. Four main areas 1) Data; 2) Human Resources; 3) Ethics and Regulation; and 4) Research and Innovation is where AI problems and potential are discovered.